Personalized in vitro Extracellular Matrix Models of Collagen VI-Related Muscular Dystrophies - Almici, Enrico; Chiappini, Vanessa; López-Márquez, Arístides; Badosa, Carmen; Blázquez, Blanca; Caballero, David; Montero, Joan; Natera-de Benito, Daniel; Nascimento, Andrés; Roldán, Mònica; Lagunas, Anna; Jiménez-Mallebrera, Cecilia; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Collagen VI-related dystrophies (COL6-RDs) are a group of rare congenital neuromuscular dystrophies that represent a continuum of overlapping clinical phenotypes that go from the milder Bethlem myopathy (BM) to the severe Ullrich congenital muscular dystrophy, for which there is no effective treatment. Mutations in one of the three collagen VI genes alter the incorporation of this protein into the extracellular matrix (ECM), affecting the assembly and the structural integrity of the whole fibrillar network. Clinical hallmarks of COL6-RDs are secondary to the ECM disruption and include muscle weakness, proximal joint contractures, and distal hyperlaxity. Although some traits have been identified in patients’ ECMs, a correlation between the ECM features and the clinical phenotype has not been established, mainly due to the lack of predictive and reliable models of the pathology. Herein, we engineered a new personalized pre-clinical model of COL6-RDs using cell-derived matrices (CDMs) technology to better recapitulate the complexity of the native scenario. We found that CDMs from COL6-RD patients presented alterations in ECM structure and composition, showing a significantly decreased collagen VI secretion, especially in the more severe phenotypes, and a decrease in fibrillin-1 inclusion. Collagen VI mediates the three-dimensional organization of fibronectin (FN) in the ECM. Therefore, we examined FN fibrils disposition and morphology in the CDMs. We observed that fibril alignment, length, width, and straightness are higher in patients with COL6-RDs. Overall, results indicate that CDMs models are promising tools to explore which alterations arise in the composition and fibrillar architecture due to mutations in collagen VI genes, especially in early stages of matrix organization. Ultimately, CDMs derived from COL6-RD patients may become relevant pre-clinical models, which may help identifying novel biomarkers to be employed in the clinics and to investigate novel therapeutic targets and treatments.